Applying GPU Programming to Obtain Average AS/RS Performance in Optimal Zoned Aisles - Lauck, Sebastian; Boxnick, Simon; Kopecki, Lukas (Proceedings of the IEEE Asia-Pacific World Congress on Computer Science and Engineering 2014 (APWC on CSE 2014))

Analyzing Supply Chain nodes in Heterogeneous Environments based on Transaction Data with Respect to Independent item Behavior - Lauck, Sebastian; Boxnick, Simon; Kopecki, Lukas (Proceedings of the 2nd International Conference on Advances in Computing, Electronics and Communication (ACEC-2014))

System Thinking: Crafting Scenarios for Prescriptive Analytics - Weber, Jens; Minhee, Cho; Lee, Mikyoung; Song, Sa-kwang; Geierhos, Michaela; Jung, Hanmin (Proceedings of the First International Workshop on Patent Mining and Its Applications (IPAMIN) 2014)

SentiBA: Lexicon-based Sentiment Analysis on German Product Reviews - Dollmann, Markus; Geierhos, Michaela (Konvens 2014 Workshop Proceedings)

Linked Open Data System for Scientific Data Sets - Baeumer, Frederik Simon; Gim, Jangwon; Jeong, Do-Heon; Geierhos, Michaela; Jung, Hanmin (Proceedings of the First International Workshop on Patent Mining and Its Applications (IPAMIN) 2014)

Are Requirements for Graduates of Master and PhD Programs in Business and Information Systems Engineering Changing? - Eymann, T.; Kundisch, Dennis

Should I Stay or Should I Go - Eymann, T.; Kundisch, Dennis; Recker, J.

Trade and fertility in the developing world: the impact of trade and trade structure - Gries, Thomas; Grundmann, Rainer (Journal of Population Economics)

Ändern sich die beruflichen Anforderungen an Masterabsolventen und Doktoranden der Wirtschaftsinformatik? - Eymann, T.; Kundisch, Dennis

Should I Stay or Should I Go - Herausforderungen und Chancen eines Wechsels zwischen Hochschulsystemen - Eymann, T.; Kundisch, Dennis; Recker, J.

Vorwort der Tagungsleitung - Suhl, Leena; Kundisch, Dennis

Household Savings and Productive Capital Formation in Rural Vietnam: Insurance vs. Social Network - Gries, Thomas; Dung, Ha Van (Modern Economy)

The same but not the same - Challenges in comparing patient opinions - Geierhos, Michaela; Schulze, Sabine

What is research ethics observing? An interdisciplinary {\ "a} re discussion between computational linguistics and qualitative-constructivist social research} - Geierhos, Michaela; Siri, Jasmin (Proceedings Research Ethics in Qualitative and Quantitative Social Research)

Ans {\ "a} sets for ü r an online optimization of the lot sizes in the Series production - Dangelmaier, Wilhelm

Modeling of the PLC Behavior in Intralogistics with Non-Autonomous Hybrid Petri-Nets - Kopecki, Lukas; Lauck, Sebastian

Information Systems for Composite Materials: Requirements and Challenges - Dangelmaier, Wilhelm; Sommer-Dittrich, Thomas; Streichhan, Jenny; Monhof, Markus (Applied Mechanics and Materials)

Comparative study on disambiguating acronyms in the scientific papers using the open knowledge base - Jeong, Do-Heon; Gim, Jangwon; Jung, Hanmin; Geierhos, Michaela; Baeumer, Frederik Simon (Proceedings of the 9th Asia Pacific International Conference on Information Science and Technology)

An Evolutionary Approach on Multi-objective Scheduling for Evolving Manufacturing Systems - Klöpper, Benjamin; Pater, Jan-Patrick; Dangelmaier, Wilhelm (Proceedings of the 47th Annual Hawaii International Conference on System Sciences)
New paradigms for designing manufacturing systems, such as adaptive and service-oriented manufacturing systems or self-optimizing resources, introduce new degrees of freedom into manufacturing control. These paradigms lead to the research question how human decision makers can be enabled to exploit the high adaptability of the new manufacturing systems in accordance to the current requirements arising from quickly changing market requirements and demand for sustainable manufacturing. This contribution extends a scheduling model for self-optimizing and service-oriented manufacturing systems through the consideration of alternative resources and introduces a multi-objective scheduling concept based on evolutionary algorithms in combination with a new optimized type of crossover operator.

Acceleration of Materialflow Simulations Using Model Coarsening by Token Sampling and Online Error Estimation and Accumulation Controlling - Renken, Hendrik

Towards a Local Grammar-based Persondata Generator for Wikipedia Biographies - Geierhos, Michaela (Penser le Lexique-Grammaire)

Development of the RailCab Vehicle - Flaßkamp, Kathrin; Grösbrink, Stefan; Hartmann, Philip; Heinzemann, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Krüger, Martin; Ober-Blöbaum, Sina; Priesterjahn, Claudia; Rasche, Christoph; Schäfer, Wilhelm; Steenken, Dominik; et al. (Dependability of Self-Optimizing Mechatronic Systems)

Outsourcing von Lagerdienstleistungen als operatives Entscheidungsproblem - Betz, Stefan (Logistikorientiertes Produktionsmanagement)

Beating Irrationality: Does Delegating to IT Alleviate the Sunk Cost Effect? - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (Management Science)

Using Income Accounting as the Theoretical Basis for Measuring IT Productivity - Kundisch, Dennis; Mittal, Neeraj; Nault, Barrie (Information Systems Research)

Don't take away my Status! - Evidence from the Restructuring of a Virtual Reward System - Mutter, Tobias; Kundisch, Dennis (Computer Networks)

Business Models - An Information Systems Research Agenda - Veit, Daniel; Clemons, Eric; Benlian, Alexander; Buxmann, Peter; Hess, Thomas; Kundisch, Dennis; Leimeister, Jan-Marco; Loos, Peter; Spann, Martin (Business & Information Systems Engineering)

Geschäftsmodelle - Eine Forschungsagenda für die Wirtschaftsinformatik - Veit, D.; Clemons, E.; Buxmann, A.; Hess, T.; Kundisch, Dennis; Leimeister, J.-M.; Loos, P.; Spann, M. (Wirtschaftsinformatik)

Analyzing Cost and Risk Interaction Effects in IT Project Portfolios - Heinrich, B.; Kundisch, Dennis; Zimmermann, Steffen (BIT - Banking and Information Technology)

Low Carbon Economics - Theory and application - Gries, Thomas (Low Carbon Economics)

Zur Ausbreitung und Behinderung von Epidemien - Eine Netzwerkanalyse - Drigalsky, Liesa

Finanzierung - Grundlagen, Institutionen, Instrumente und Kapitalmarkttheorie - Gräfer, Horst; Schiller, Bettina; Rösner, Sabrina
Dieses Lehr- und Arbeitsbuch präsentiert Ihnen die wichtigsten Grundlagen der Unternehmensfinanzierung auf dem neuesten fachlichen Stand. Der perfekte Einstieg in ein zentrales finanzwirtschaftliches Fach- und Praxisgebiet – mit vielen Beispielen und Übungen.
Keywords: Management; Wirtschaft

IT-basierte Dienstleistungen für die Elektromobilität --- Konzeptioneller Rahmen und Literaturanalyse - Klör, Benjamin; Bräuer, Sebastian; Beverungen, Daniel; Matzner, Martin (Proceedings of the Multikonferenz Wirtschaftsinformatik 2014 (MKWI 2014))

Towards a Flexible and Privacy-Preserving Reputation System for Markets of Composed Services - Brangewitz, Sonja; Jungmann, Alexander; Petrlic, Ronald; Platenius, Marie Christin (Proceedings of the 6th International Conferences on Advanced Service Computing (SERVICE COMPUTATION))
One future goal of service-oriented computing is to realize global markets of composed services. On such markets, service providers offer services that can be flexibly combined with each other. However, most often, market participants are not able to individually estimate the quality of traded services in advance. As a consequence, even potentially profitable transactions between customers and providers might not take place. In the worst case, this can induce a market failure. To overcome this problem, we propose the incorporation of reputation information as an indicator for expected service quality. We address On-The-Fly Computing as a representative environment of markets of composed services. In this environment, customers provide feedback on transactions. We present a conceptual design of a reputation system which collects and processes user feedback, and provides it to participants in the market. Our contribution includes the identification of requirements for such a reputation system from a technical and an economic perspective. Based on these requirements, we propose a flexible solution that facilitates the incorporation of reputation information into markets of composed services while simultaneously preserving privacy of customers who provide feedback. The requirements we formulate in this paper have just been partially met in literature. An integrated approach, however, has not been addressed yet.

On the Ontological Expressiveness of Conceptual Modeling Grammars for Service Productivity Management - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Peter Rauer, Hans; Sigge, Daniel (Information Systems and e-Business Management)

Exploring the Interplay of the Design and Emergence of Business Processes as Organizational Routines - Beverungen, Daniel (Business and Information Systems Engineering)

Über das Zusammenwirken der Gestaltung und Emergenz von Geschäftsprozessen als Organisationsroutinen - Beverungen, Daniel (WIRTSCHAFTSINFORMATIK)

The Interaction of Signals: A Fuzzy set Analysis of the Video Game Industry - Kaimann, Daniel; Cox, Joe
Customers continuously evaluate the credibility and reliability of a range of signals both separately and jointly. However, existing econometric studies pay insufficient attention to the interactions and complex combinations of these signals, and are typically limited as a result of difficulties controlling for multicollinearity and endogeneity in their data. We develop a novel theoretical approach to address these issues and study different signaling effects (i.e., word-of-mouth, brand reputation, and distribution strategy) on customer perceptions. Using data on the US video games market, we apply a fuzzy set qualitative comparative analysis (fsQCA) to account for cause-effect relationships. The results of our study address a number of key issues in the economics and management literature. First, our results support the contention that reviews from professional critics act as a signal of product quality and therefore positively influence unit sales, as do the discriminatory effects of prices and restricted age ratings. Second, we find evidence to support the use of brand extension strategies as marketing tools that create spillover effects and support the launch of new products.

The Economics of Individual Behavior in Competitive Environments: Empirical Evidence from Real-Life Tournaments - Scheel, Friedrich

Customer collectives in healthcare: The transformative potential of service to overcome consumer vulnerability - Rötzmeier-Keuper, Julia; Wünderlich, Nancy (Proceedings of the 39th Annual Macromarketing Conference)

Interdependent Relationships Between and among Service Providers and Customer Collectives. - Rötzmeier-Keuper, Julia; Wünderlich, Nancy (Proceedings of the AMA SERVSIG International Service Research Conference)

Strategic and Cooperative Games in Network Economics - Röhl, Nils

Signalisieren und Screening in Arbeitsmärkten - die Experimente von Brandts & Holt und Kübler et. al - Kaiser, Sarah

The challenge of assessing the market value of private companies using a standardised combination method for tax purposes--Lessons to be learnt from past experience - Müller, Jens (European Accounting Review)
When taxes on capital or wealth are levied, in most countries companies have to be assessed in terms of their market value (MV). Estimating the MV of private companies for tax purposes is a challenging task for tax authorities as MVs are not available. In this study, I empirically analyse to what extent an accounting-based tax valuation method for private companies, a simplified residual income model, succeeds in matching the MV. I refer to the mandatory Standardised Combination Model that is a special case of methods commonly used in several countries. In the absence of market prices for private companies, I use a sample of small German public companies as a proxy. I validate this approach using a sensitivity analysis that involves matching the sample of public companies with that of private companies. The results imply that the mandatory Standardised Combination Model leads to a severe unequal treatment not only between public and private companies but also among private companies across and within industries. Furthermore, I simulate the effects of variation in the key parameters and highlight their impact on the approximation quality of the Standardised Combination Method. The findings are relevant to tax reform discussions as well as to tax policy-makers and practitioners in many countries.
Keywords: Challenge of Assessing; Tax Purposes

Provider Competition in Infrastructure-as-a-Service - Künsemöller, Jörn; Brangewitz, Sonja; Karl, Holger; Haake, Claus-Jochen (Proceedings of the 2014 IEEE International Conference on Services Computing (SCC))
This paper explores how cloud provider competition inﬂuences instance pricing in an IaaS (Infrastructure-as-a-Service) market. When reserved instance pricing includes an on-demand price component in addition to a reservation fee (two-part tariffs), different providers might offer different price combinations, where the client’s choice depends on its load proﬁle. We investigate a duopoly of providers and analyze stable market prices in two-part tariffs. Further, we study offers that allow a speciﬁed amount of included usage (three-part tariffs). Neither two-part nor three-part tariffs produce an equilibrium market outcome other than a service pricing that equals production cost, i.e., complex price structures do not signiﬁcantly affect the results from ordinary Bertrand competition.

Behavioral Mechanisms Prompted by Badges: The Goal-Gradient Hypothesis - Mutter, Tobias; Kundisch, Dennis (Proceedings of the International Conference on Information Systems (ICIS))

The Hunt for Quality in a Market: Exploring the Relationship between Local Market Structure and Digitized Customer Experience - Herrmann, Philipp

Too Much of a Good Thing? Welfare Consequences of Market Transparency - Gu, Yiquan; Hehenkamp, Burkhard (Journal of Institutional and Theoretical Economics JITE)
This paper studies welfare consequences of consumer-side market transparency with endogenous entry of firms. Different from most studies, we consider the unique symmetric entry equilibrium, which is in mixed strategies. We identify two effects of market transparency on welfare: a competition effect and a novel market-structure effect. We show, surprisingly, that for almost all demand functions the negative market-structure effect eventually dominates the positive competition effect as the market becomes increasingly transparent. Consumer-side market transparency can therefore be socially excessive even without collusion. The only exception among commonly used demand functions is the set of constant demand functions.

The Hunt for Quality in a Market: Exploring the Relationship between Local Market Structure and Digitized Customer Experience - Herrmann, Philipp; Rahman, Mohammad (Workshop on Information Systems & Economics (WISE))

Modeling Languages for Business Models as Tools for Innovation: Towards a Theoretical Foundation - John, Thomas (Proceedings of the Americas' Conference on Information Systems (AMCIS))